Nilai Budaya Lampung (Piil Pesenggiri) dalam Sastra Lisan Pepaccur Masyarakat Lampung Pepadun dalam Prosesi Pengambilan Gelar Adat - Ratnaningsih, Dewi (JURNAL PESONA, 2019)
Pepaccur is a Lampung poetry which contains advices or messages delivered in the ceremony of giving customary titles. In this study, data was collected from several areas belonging to the Lampung Abung community, such as Kotabumi Ilir, Blambangan Pagar, Surakarta, Bumi Agung, and Mulang Maya. The problem that will be examined in this study is the cultural values of Lampung contained in Pepaccur. The purpose and benefits of this research are (1) to know the cultural values contained in Pepaccur in the Pepadun community in the procession of taking customary titles; (2) to revitalize Pepaccur in the Pepadun Lampung community. Descriptive method through qualitative approach is the method used in this study. Data collection techniques used in this study were (1) Observations, (2) Recording, and (3) Interviews. The data analysis technique is done by identifying the cultural values of Lampung (piil pesengiri) in Pepaccur. Based on the ethnographic study that was used as a foothold in this study, the cultural values contained in Pepaccur contain advice or messages of life called piil-pesenggiri. Piil-pesenggiri itself consists of: (1) meeting nyimah, (2) nengah nyappur, (3) sakai, (4) waving, and (5) juluk adek.